THE EFFECT OF PROJECT-BASED SUKUK ISSUANCE ON THE HUMAN DEVELOPMENT INDEX IN INDONESIA - Prayitno, Anang Dwi (Universitas Suryakancana, 2026)
Penelitian ini bertujuan untuk mengidentifikasi perkembangan pembiayaan infrastruktur melalui project based sukuk (PBS) dan dampaknya terhadap indikator pembangunan manusia di Indonesia. Efektivitas belanja pemerintah dan pembiayaan pembangunan merupakan aspek penting untuk dikaji karena pemerintah secara konstitusional bertanggung jawab untuk meningkatkan kesejahteraan masyarakat. Analisis yang dilakukan meliputi pendekatan kuantitatif dengan memanfaatkan data sekunder yang dikumpulkan dari sumber-sumber relevan. Analisis kuantitatif dimulai dari statistik deskriptif dan dilanjutkan dengan perhitungan elastisitas dan estimasi regresi. Hasilnya menunjukkan bahwa pembiayaan infrastruktur melalui project base sukuk (PBS) meningkat pada periode 2015-2024. Hal serupa juga terjadi pada perkembangan Indeks Pembangunan Manusia (IPM). Regresi data time series membuktikan bahwa pengeluaran pemerintah mempunyai dampak yang signifikan dan positif terhadap peningkatan IPM dan kesejahteraan ekonomi masyarakat. IPM dan belanja riil per kapita bersifat inelastis terhadap pembiayaan infrastruktur melalui project base sukuk (PBS). This study aims to identify the development of infrastructure financing through project based sukuk (PBS) and its impact on human development indicators in Indonesia. The effectiveness of government spending and development financing is an important aspect to study because the government is constitutionally responsible for improving people's welfare. The analysis carried out includes a quantitative approach by utilizing secondary data collected from relevant sources. Quantitative analysis starts from descriptive statistics and continues with elasticity calculations and regression estimation. The results show that infrastructure financing through project base sukuk (PBS) increased in the 2015-2024 period. The same thing also happened in the development of the Human Development Index (HDI). Time series data regression proves that government spending has a significant and positive impact on increasing HDI and people's economic welfare. HDI and real expenditure per capita are inelastic to infrastructure financing through project base sukuk (PBS).